Gewerkschaften und Arbeitgeberverbände: Organisationsgrade, Tarifbindung und Einflüsse auf Löhne und Beschäftigung - Claus Schnabel (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– In Germany, trade unions and employers' associations play a role not only in wage determination but also in issues of social policy and labour law. While the majority of firms are organized in employers' associations, less than one quarter of employees are members of a trade union. Both social partners have severe problems in recruiting and keeping members. Union and employers' association densities as well as bargaining coverage are declining. Despite this erosion, collective agreements are still relevant for five out of six employees because they constitute an anchor of wage setting even for firms that are not formally bound by collective agreements. Empirical studies show that the social partners and collective bargaining exert a significant effect on wages. There are signs, however, that the power and influence of the social partners is increasingly endangered.
Keywords: 330; Lohnfindung; Lohnhöhe; Tarifbindung; Sozialpartner; Arbeitgeberverband; Arbeitgebervertretung; Arbeitnehmervertretung; Gewerkschaft; Organisationsgrad; Gewerkschaftszugehörigkeit; Beschäftigungseffekte